Gallium-doped zinc oxide prepared by the Pechini method. - Goncalves, A. D. (2002)
Gallium-doped zinc oxide (ZnO:Ga) was prepared by the Pechini method from zinc citrate and gallium hydroxide. By this method, it is possible to synthesize crystalline ZnO:Ga by firing the polymeric precursor in air at 900degreesC for four hours. The homogeneous resin containing 2% of dopant could be obtained only with the addition of the ethylenediaminetetraacetic acid (edta). The size of oxide particles, also, was diminished by the addition of edta.